Automatic solar fence lighting / Muhammad Arif Senri Mohd Shahar and Wan Mohamad Farhan Mohamad Shukor - Mohd Shahar, Muhammad Arif Senri; Mohamad Shukor, Wan Mohamad Farhan (2013)
Automatic solar fence lighting is a device that will operate automatically in order to light up the house surrounding area. This is because the dark surrounding of a house can attract criminals to commit crimes especially burglary. Automatic solar fence lighting also help people to save more money and energy by using reusable solar energy as a main power supply for this device to operate. In daylight, when the light beam from the sun strike on the solar panel, it will be converted into electricity to charge the 12v rechargeable battery up and this charging process will be controlled by another device called charger controller. This charger controller monitors the charging process so that the battery will not be overcharged. At night, Light Dependent Resistor (LDR) detects the low presence of light intensity then it will be activated the lighting circuit to light up the fence lights throughout the night until it detects the presence of light that will turn off the lights back.